The Effectiveness of AI Applications in Enhancing Students’ Learning Interest: A Case Study at Universitas Muslim Maros - Rika Riyanti; Rizki Amalia Nur; Anna Majid (Didaktika: Jurnal Kependidikan, 2025)
This study aims to determine the extent to which students at Universitas Muslim Maros utilize Artificial Intelligence (AI)-based applications in the learning process, as well as to evaluate their impact on enhancing learning interest. The background of this research is grounded in the rapid advancement of digital technology, which has driven transformation in the field of education, particularly in how students access and manage information. This study employs a descriptive qualitative approach, with data collected through observation, questionnaires, and in-depth interviews. It also aims to analyze the relationship between the use of AI applications (variable X) and students' learning interest (variable Y), as well as to measure the effectiveness of AI in the context of higher education learning. The results of the study show that out of a total of 148 respondents, 44 students stated “agree” and 57 students stated “strongly agree” regarding the use of AI in learning activities. The percentage of agreement based on the index reached 53.5%, indicating that the majority of students support the use of AI applications as learning tools. Based on these findings, it can be concluded that the use of Artificial Intelligence technology significantly contributes to increasing the learning interest of students at Universitas Muslim Maros.